The Impact of Drought Stress on Antioxidant Responses and Accumulation of Flavonolignans in Milk Thistle (Silybum marianum (L.) Gaertn) - ElSayed, Abdelaleim I. (Plants (Basel), 2019)
Biosynthesis and accumulation of flavonolignans in plants are influenced by different environmental conditions. Biosynthesis and accumulation of silymarin in milk thistle (Silybum marianum L.) were studied under drought stress with respect to the antioxidant defense system at the physiological and gene expression level. The results revealed a reduction in leaf chlorophyll, ascorbic acid, and glutathione contents. In contrast, H(2)O(2), proline, and antioxidative enzyme activities, such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX), and glutathione reductase (GR), were increased. These results confirmed that milk thistle undergoes oxidative stress under drought stress. Furthermore, transcription levels of APX, SOD, CAT, 1-Cys-Prx, and PrxQ were significantly increased in milk thistle under drought stress. Overall this suggests that protection against reactive oxygen species and peroxidation reactions in milk thistle are provided by enzymatic and non-enzymatic antioxidants. Flavonolignans from milk thistle seeds after different drought treatments were quantified by high-performance liquid chromatography (HPLC) and showed that severe drought stress enhanced the accumulation of silymarin and its components compared with seeds from the control (100% water capacity). Silybin is the major silymarin component and the most bioactive ingredient of the milk thistle extract. Silybin accumulation was the highest among all silymarin components in seeds obtained from drought-stressed plants. The expression of the chalcone synthase (CHS) genes (CHS1, CHS2, and CHS3), which are associated with the silybin biosynthetic pathway, was also increased during drought stress. These results indicated that milk thistle exhibits tolerance to drought stress and that seed derived from severe drought-stressed plants had higher levels of silymarin.